Pembinaan Akhlak Terhadap Peserta Didik - Rahmiyatul Husna (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research on moral development of students at Nibras Islamic Elementary School, Padang City aims to find out and describe moral development at Nibras Islamic Elementary School with several problem formulations, namely (1) How is moral development towards Allah SWT at Nibras Islamic Elementary School, Padang City? How is the moral development of Rasulullah SAW at Nibras Islamic Elementary School, Padang City? How is the moral development of fellow humans at Nibras Islamic Elementary School, Padang City? and How is moral development in nature at Nibras Islamic Elementary School, Padang City? This research uses a qualitative method with a descriptive approach. The informants in this research were educators, students, school principals and parents of students. The data collection techniques used were interviews, observation and documentation. Testing the validity of the data using a credibility test. The data analysis technique used is data collection, data reduction, data presentation and drawing conclusions. Based on the research results, it was found that (1) Moral development towards Allah at Nibras Islamic Elementary School is by getting used to several practices, namely the habit of praying in congregation, recitations and memorizing the Koran, reciting the Pledge, practicing Asmaul Husna, giving donations and sharing sustenance, reading prayers in daily life and in the past (2) Moral development for Rasulullah at Nibras Islamic Elementary School by instilling a sense of love for Rasulullah, enlivening the Prophet's sunnah, following Rasulullah who always conveyed goodness or preaching (3) Moral development for fellow humans at Nibras Islamic Elementary School by instilling a principle that every individual is obliged to provide comfort for themselves and comfort to fellow Muslims. (4) Developing Morals towards Nature at Nibras Islamic Elementary School by getting into the habit of keeping the classroom and school environment clean, throwing away rubbish in its proper place, not destroying or disturbing plants, and loving animals as living creatures created by Allah SWT.